Egg freezing for non-medical uses: the lack of a relational approach to autonomy in the new Israeli policy and in academic discussion. Issue 3 (1st October 2011) - Shkedi-Rafid, Shiri; Hashiloni-Dolev, Yael
Abstract : Recently, the Israel National Bioethics Council (INBC) issued recommendations permitting egg freezing to prevent both disease- and age-related fertility decline. The INBC report forms the basis of Israel's new policy, being one of the first countries to regulate and authorise egg freezing for what it considers to be non-medical (ie, social) uses. The ethical discussion in the INBC report is reviewed and compared with the scant ethical discourse in the academic literature on egg freezing as a means of preventing age-related loss of fertility. We argue that both the INBC recommendations and the bioethical academic discourse on egg freezing are grounded in liberal ideology, which views technology as primarily enabling. Accordingly, they promote 'individual autonomy' as exercised through informed consent. Our study suggests that a relational approach to autonomy may be a more suitable model for considering women's choices about egg freezing.